Filling the Power Supply Gap in Africa: Is Natural Gas the Answer? - Ishmael Ackah; Freda Akyeabea Opoku (African Governance and Development Institute (AGDI), 2016)
Purpose: The purpose of this paper is to review the reserves and production of natural gas in Africa and evaluate how it can help solve the power challenges of the continent. Design/Methodology: This paper develops from a descriptive analysis and literature on natural gas and power. Findings: The key finding is that despite increased discovery of natural gas in Africa, it has had minimal impact on power production. Limitations:This study provides a descriptive overview and is limited to only natural gas. It does not consider how other energy sources can contribute to solving Africa's power challenges. Policy implications: This paper will draw the attention of both policy makers and the investment community to the opportunities in the `natural gas- power' value chain and the need to invest in gas infrastructure. Originality: An overview of the power challenges and natural gas potential of Africa is provided.
Keywords: Q32; Q35; Q41; Q48; Q49; 330; Natural Gas; Power Generation; Africa